Penerapan Fatwa DSN MUI pada Pembiayaan Murabahah BPRS Hasanah Pekanbaru - Mohd Winario; Husni Fuaddi (ISLAMIC BUSINESS and FINANCE (IBF), 2020)
The research was based on a phenomenon that occurred in the community on the response that murabahah financing in Islamic banks is the same as loan transactions at conventional banks. It is also supported by the existence of the MUI DSN fatwa regulating murabahah financing. This research aims to know whether implementing murabahah financing is based on Islamic principles and whether it is under the fatwa set by the DSN-MUI. This research was conducted at BPRS Hasanah Pekanbaru. This study employed a qualitative descriptive analysis. The sampling method used snowball sampling. This research used interviews, observation, and documentation to collect data. The results showed that PT. BPRS Hasanah Pekanbaru in implementing murabahah financing is under the DSN-MUI Fatwa. Hence, it is necessary to increase caution in its implementation so that BPRS will continue being consistent in its Syariah and captivate the hearts of customers